2019
DOI: 10.1111/chd.12741
|View full text |Cite
|
Sign up to set email alerts
|

S100B and its relation to cerebral oxygenation in neonates and infants undergoing surgery for congenital heart disease

Abstract: Objectives: Neonates and infants undergoing surgery for congenital heart disease are at risk for developmental impairment. Hypoxic-ischemic brain injury might be one contributing factor. We aimed to investigate the perioperative release of the astrocyte protein S100B and its relation to cerebral oxygenation.Methods: Serum S100B was measured before and 0, 12, 24, and 48 hours after surgery. Cerebral oxygen saturation was derived by near-infrared spectroscopy. S100B reference values based on preoperative samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
(210 reference statements)
1
3
0
Order By: Relevance
“…In our study, we have identified statistically significantly increased values of S100B postoperatively with no correlation between cerebral oxygen saturation or neurodevelopmental scores and S100B. As Hansen et al showed in a study, postoperative levels of S100B were increased in about 40% of newborns and children with CHD [31]. Increased S100B values after surgery in children with CHD have been associated with neurological impairment [9,11,38].…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…In our study, we have identified statistically significantly increased values of S100B postoperatively with no correlation between cerebral oxygen saturation or neurodevelopmental scores and S100B. As Hansen et al showed in a study, postoperative levels of S100B were increased in about 40% of newborns and children with CHD [31]. Increased S100B values after surgery in children with CHD have been associated with neurological impairment [9,11,38].…”
Section: Discussionsupporting
confidence: 49%
“…Children with increased postoperative S100B levels also had impaired perioperative cerebral tissue oxygenation. In newborns, no relationship was found between S100B and cerebral oxygenation [31].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The following biomarkers are being focused on: matrix metalloproteinases (MMPs), transforming growth factor β (TGF-β), tissue inhibitors of matrix metalloproteinases (TIMPs), alpha1antitrypsin, as well as non-coding microRNAs (47,48). Cluster III represented biomarkers in secondary injury after cardiopulmonary bypass in children with CHD, such as Neutrophil gelatinase-associated lipocalin (NGAL) and SB100 protein, which mainly involved the prediction and evaluation of kidney injury and brain injury after extracorporeal circulation (49,50). The concentration of NGAL in urine and serum represents a sensitive, specific and highly predictive early biomarker of acute kidney injury after cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%